User Involvement in Information System Development: A Conflict Model and Empirical Test - Robey, Daniel; Farrow, Dana (Management Science, 1982)
This research explores the relationships among user participation, influence, conflict, and conflict resolution in the development of management information systems. Three stages of development are analyzed: initiation, design, and implementation. Results show that influence does result from user participation, and that influence leads to both conflict and resolution. Participation without influence, however, does not lead to successful conflict resolution in any of the three development stages.